CLOCK SYNCHRONIZATION: TIME PRECISION PROTOCOL AND ITS EMPLOYMENT IN IOT ENVIRONMENTS - Santander Durán, Beatriz (Telemática, 2020)
The implementation of the Internet of Things (IoT) will change the daily life of its users by allowing the exchange of data between generalized things over the Internet. Regarding this, unless you are an expert on networks, synchronization is probably more familiar as a term used with wristwatches, than as an IoT term, however, the future of this may depend on this issue. In a world on demand where immediate results are expected, a bad synchronization method in a critical environment can end the information created only a few seconds before. This presentation is not specifically about IoT, but it sets out a reference framework on the use of an efficient synchronization method in the network infrastructure that would support it since a bad timing can lead to call and link drops, corruption, data losses, and retransmissions; videos that do not play, interrupting games, car accidents directed by GPS, among other examples.